2021
DOI: 10.1186/s12934-021-01717-w
|View full text |Cite
|
Sign up to set email alerts
|

Production of 9,21-dihydroxy-20-methyl-pregna-4-en-3-one from phytosterols in Mycobacterium neoaurum by modifying multiple genes and improving the intracellular environment

Abstract: Background Steroid drugs are essential for disease prevention and clinical treatment. However, due to intricated steroid structure, traditional chemical methods are rarely implemented into the whole synthetic process for generating steroid intermediates. Novel steroid drug precursors and their ideal bacterial strains for industrial production have yet to be developed. Among these, 9,21-dihydroxy-20-methyl-pregna-4-en-3-one (9-OH-4-HP) is a novel steroid drug precursor, suitable for the synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…The productivity of these strains could be further improved by the use of mycobacterial resting cells [ 41 – 44 ]. Very recently, an engineered strain of M. neoaurum DSM 44074 could efficiently convert phytosterols to 9OH-BA [ 45 ]. These investigations have revealed that the dual competing pathways between the overwhelming C19 steroid pathway and the C22 steroid pathway are involved in phytosterol sidechain degradation [ 22 , 24 , 45 48 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The productivity of these strains could be further improved by the use of mycobacterial resting cells [ 41 – 44 ]. Very recently, an engineered strain of M. neoaurum DSM 44074 could efficiently convert phytosterols to 9OH-BA [ 45 ]. These investigations have revealed that the dual competing pathways between the overwhelming C19 steroid pathway and the C22 steroid pathway are involved in phytosterol sidechain degradation [ 22 , 24 , 45 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, an engineered strain of M. neoaurum DSM 44074 could efficiently convert phytosterols to 9OH-BA [ 45 ]. These investigations have revealed that the dual competing pathways between the overwhelming C19 steroid pathway and the C22 steroid pathway are involved in phytosterol sidechain degradation [ 22 , 24 , 45 48 ]. Some key specific genes, such as hsd4A [ 14 ], fadA5 [ 13 , 14 ], Sal [ 49 ], hsaG [ 50 ] and OpccR [ 13 ], were involved in controlling metabolic flux between the two pathways (Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, kstD3 has no catalytic capacity for 9-OHAD, but has high dehydrogenation activity for saturated A-ring and produces 1,4-diene structure. Similarly, KstDs with diversi ed functions has been found in many steroid producers, such as M. neoaurum ATCC25795 [18], M. neoaurum DSM1381 [9], A. simplex CGMCC14539 [42], Mycobacterium smegmatis [32,34], etc. This residual KstD activity becomes more complex due to the redundancy of KstD enzymes and the rich substrate spectrum characteristics.…”
Section: Evaluation Of 9-ohad Producermentioning
confidence: 99%
“…The change of NADH/NAD + level could lead to the opposite catalytic function. Furthermore, the lack of activity Hsd4A could also lead part of the steroids ow to the C22 pathway, and nally, 9-OHHP is generated [21,42]. Moreover, a new biosynthetic mechanism of 4-HP was deciphered in the steroids degradation pathway of M. neoaurum CCTCC AB2019054, the C-terminal domain of mnOpccr converts 3-OPC-CoA to 3-OPA, and the Nterminal domain further restores 3-OPA to 4-HP [22].…”
Section: Evaluation Of 9-ohad Producermentioning
confidence: 99%
See 1 more Smart Citation